DNA Methylation Analysis to predict Regression of high-grade anal Intraepithelial Neoplasia in HIV+ men (MARINE): a cohort study protocol. Issue 8 (3rd August 2022) - Dias Gonçalves Lima, Fernando; van der Zee, Ramon P; Dick, Stèfanie; van Noesel, Carel J M; Berkhof, Johannes; Schim van der Loeff, Maarten F; Prins, Jan M; Steenbergen, Renske D M; de Vries, Henry J C
Abstract : Introduction: Anal cancer precursors, or high-grade anal intraepithelial neoplasia (HGAIN), are highly prevalent in HIV-seropositive (HIV+) men who have sex with men (MSM). Around 30% of lesions regress within 1 year, but current histopathological assessment is unable to distinguish between HGAIN likely to regress and HGAIN likely to persist or progress to cancer. We aim to assess if host cell DNA methylation markers can predict regression of HGAIN, thus determining the need for immediate treatment or active surveillance. This could reduce overtreatment and the associated anal and psycho-sexual morbidity. Methods and analysis: This is an active surveillance cohort study in three centres located in Amsterdam, the Netherlands, in 200 HIV+ MSM diagnosed with HGAIN. Participants will not be treated, but closely monitored during 24 months of follow-up with 6 monthly visits including cytology, and high-resolution anoscopy with biopsies. The primary study endpoint is histopathological regression of each baseline HGAIN lesion at the end of the study. Regression is defined as ≤low grade anal intraepithelial neoplasia in the exit biopsy at 24 months. Regression proportions in lesions with low versus high methylation levels ( ASCL1, ZNF582 ), other biomarkers (HPV genotype, HPV-E4, p16 INK4A, Ki-67) and immunological markers at baseline will be compared. Main secondary endpoints are the histological and clinical outcome (ie, the number of octants affected by HGAIN) of each baseline HGAIN lesion and overall HGAIN disease (i.e., all lesions combined) after each visit. The health-related quality of life of the study group will be compared with that of a control group of 50 HIV+ MSM receiving regular HGAIN treatment. Ethics and dissemination: Ethics approval was obtained from the Institutional Review Board of the Academic Medical Center (Amsterdam, The Netherlands; reference no. 2021_099). Participants are required to provide written informed consent. Findings will be disseminated through publication in peer-reviewed scientific journals and presentations at international scientific conferences; dissemination to policy makers and the target patient group will be achieved through our (inter-)national network, professional associations and collaboration with a patient representative organisation. Trial registration number: NL9664.